Skewed X-inactivation patterns in ageing healthy and myelodysplastic haematopoiesis determined by a pyrosequencing based transcriptional clonality assay. Issue 2 (20th January 2013) - Mossner, Maximilian; Nolte, Florian; Hütter, Gero; Reins, Jana; Klaumünzer, Marion; Nowak, Verena; Obländer, Julia; Ackermann, Katrin; Will, Silke; Röhl, Henning; Neumann, Uwe; Neumann, Martin; et al.
Abstract : Background: Investigation of X-chromosome inactivation patterns (XCIP) by determination of differential CpG-methylation has been widely applied for investigation of female cell clonality. Using this approach the clonal origin of various tumours has been corroborated. Controversially, strong age-related increase of peripheral blood (PB) cell clonality in haematologically healthy female subjects was reported. Recently, transcriptional XCIP ratio analysis challenged these results and questioned the suitability of methylation based clonality assays. Methods: To reinvestigate XCIP-skewing in CD34, low-density mononuclear bone marrow (BM) as well as PB cells from healthy female subjects and patients with myelodysplastic syndromes (MDS), we established a transcriptional assay using pyrosequencing technique for quantification of single nucleotide polymorphism allele frequencies, representative for XCIP ratios. Results: Our assay provides high sensitivity for XCIP ratio assessment as determined by standard curves, reproducibility, inter-marker correlation as well as correlation with the DNA-methylation based human androgen receptor (HUMARA) assay. Notably, in agreement with most studies investigating this issue, significant age-related increase of XCIP skewing in PB cells from healthy elderly female subjects was confirmed. Moreover, XCIP ratio analysis suggests even stronger clonal manifestation in BM and CD34 cells. In MDS, XCIP skewing levels were distinctively elevated as compared with controls of similar age and higher degrees were associated with poor clinical outcome. Conclusions: Transcriptional clonal profiling via pyrosequencing allows accurate assessment of XCIP ratios, confirms the validity of the DNA-methylation based HUMARA assay and reveals important insights into ageing healthy and myelodysplastic haematopoiesis.